1970
DOI: 10.1021/jo00827a026
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate addition reactions of ethyl atropate with certain alkali nucleophiles. Alkylations

Abstract: Ethyl atrópate, CH^CCCeHsjCOOCaHs, underwent conjugate addition with phenylmagnesium bromide and with alkali diand triphenylmethides to form corresponding /3-substituted products. Ethyl atrópate also underwent conjugate additions with the 1,2-dialkali salts of benzophenone and benzophenone anil to afford a lactone and a -amino ester, respectively. Several new /3-amino esters were prepared by similarly condensing ethyl atrópate with certain alkali amides or with appropriate free amines. Various alkylations of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1970
1970
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to previous reports, in the case of Grignard reagents, both 1,2-and 1,4-additions were possible, 8,9 the orientation depended on some effects such as the bulk of the substrates and reagents. Although many researches have been carried out on the subject by different authors no absolute conclusion can be reached.…”
mentioning
confidence: 73%
“…According to previous reports, in the case of Grignard reagents, both 1,2-and 1,4-additions were possible, 8,9 the orientation depended on some effects such as the bulk of the substrates and reagents. Although many researches have been carried out on the subject by different authors no absolute conclusion can be reached.…”
mentioning
confidence: 73%
“…For example, promoted by SmI 3 α-chloroketones can react with aldehyde to give α,β-unsaturated ketones; 4 Sasai reported that 1-chloro-2-heptanone is able to react with benzaldehyde to form α-chloro-β-hydroxy ketones at catalysis of Sm(HMDS); 5 at the aid of Sm(OTf) 3 and s-BuLi methyliodide has been added to carbonyl group of acetophenone, 6 Our group have also reported several methods on the application of samarium(III) species in organic synthesis. 7 Here we wish to report the addition of ω-bromoacetophenone to α,β-unsaturated alkynones mediated by SmI 3 to afford Michael addition products (Scheme 1).According to previous reports, in the case of Grignard reagents, both 1,2-and 1,4-additions were possible, 8,9 the orientation depended on some effects such as the bulk of the substrates and reagents. Although many researches have been carried out on the subject by different authors no absolute conclusion can be reached.…”
mentioning
confidence: 93%
“…Many other reaction conditions and bases such as potassium t-butoxide/t-butanol, 11 sodium ethoxide/ethanol, 33 and Table Selected Physical aluminum oxide 34 which have been successfully used in other related Michael reactions, either gave poor yields, side products, polymerization, or failed to react with our substrate.…”
mentioning
confidence: 99%